What are the main lessons from Indonesia's CSR financial literacy education investment for early childhood? - Solehudin, Rd. Heri; Darmayanti, Rani (Jurnal Caksana : Pendidikan Anak Usia Dini, 2018)
Early financial literacy education helps kids internalise knowledge and receive practical cash management experience. A positive financial culture and habits that will shape their financial behaviour, including money value and meaning, are fostered. Financial literacy is essential for making decisions, especially daily activities like saving and investing. Financial literacy is taught to children early on to help them manage their money. This study examines investing approaches for early financial literacy training in Indonesia with children. This researcher uses literature. The review uses Miles and Huberman's 2010–2018 papers analysis in a Descriptive Qualitative Systematic Literature Review (SLR). These articles examine Google Scholar search results for "Financial Literacy" and "PAUD," "PAUD Financial Literacy" and "Educational Program," and "PAUD Financial Literacy" and "Investment Program" with an emphasis on early childhood education's "Investment Program." App deployment/operation: Harzing aids searches. Between 2010 and 2018, respectable national and international magazines published the articles. This study focuses on PAUD Early Childhood Education Play Group (KB) and Kindergarten (TK) programs. Find free, 25-citation, detailed, and downloadable PDF scholarly articles—research findings concern methods. Class action evaluations use descriptive qualitative research methods. According to research, the government and private sector implement financial literacy education in Indonesia. Financial literacy education approach implementation focuses on two areas: Provide online, printable financial literacy educational resources for early childhood that educators and parents may use to teach children—and second, conduct financial literacy training for early childhood educators in PAUD institutions through the private sector's CSR program. The government must adopt the PAUD teacher financial literacy socialisation program. A well-designed approach to financial literacy instruction in early infancy that emphasises social interaction, PAUD school-level financial literacy programs, and effective monitoring and evaluation measures can improve financial literacy knowledge.